2021
DOI: 10.1111/jre.12883
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin loaded chitosan guided bone regeneration membranes stimulate bone healing

Abstract: Background and Objective Electrospun chitosan membranes (ESCM) modified with short‐chain fatty acids have the ability to control the release of simvastatin (SMV), an anti‐cholesterol drug with osteogenic potential, for guided bone regeneration (GBR) applications. This study evaluated in vivo osteogenic effects of rapid short release of SMV (4 weeks) vs long sustained release (8 weeks) from acetic anhydride (AA)—and hexanoic anhydride (HA)‐modified ESCMs, respectively. Methods AA ESCMs loaded with 10 or 50 µg S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…ESCMs were fabricated as previously described [ 28 , 47 , 61 ]. Briefly, a 5.5 ( w/v )% Chitosan (Primex, Siglufjörður, Iceland) (71% DDA, MW = 311.5 kDa) was dissolved in trifluoroacetic acid/dichloromethane (TFA/DCM) (7:3) solution and mixed overnight on shaker at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ESCMs were fabricated as previously described [ 28 , 47 , 61 ]. Briefly, a 5.5 ( w/v )% Chitosan (Primex, Siglufjörður, Iceland) (71% DDA, MW = 311.5 kDa) was dissolved in trifluoroacetic acid/dichloromethane (TFA/DCM) (7:3) solution and mixed overnight on shaker at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Our past studies have demonstrated electrospun chitosan membranes (ESCM) are successful in tissue engineering applications for bone regeneration and burn wound treatment [ 27 , 28 , 29 ]. Because of their biomimetic fibrous structure and potential for drug delivery, these membranes may be further modified to help enhance their bioactivity to support skin healing and re-epithelialization that would lead to improved burn wound healing performance.…”
Section: Introductionmentioning
confidence: 99%
“…It has unique characteristics that are biocompatible, stable, biodegradable, has antimicrobial, and immunostimulatory properties [8], [9]. Because Hydroxyapatite is an inorganic scaffold biomaterial, while chitosan and gelatin are biodegradable polymers that make good additions to the sturdy HA scaffold [13], [14], [15], [16], [17], [18], [19], [20], [21].…”
Section: Utilization Of Chitosan As Bone Scaffoldmentioning
confidence: 99%
“…Loading drugs into the membranes directly or via nanoparticles can efficiently inhibit bacterial proliferation [ 20 , 21 , 22 ]. Chang et al [ 23 ] developed gelatin/hyaluronic acid-based hydrogel membranes loaded with hinokitiol.…”
Section: Introductionmentioning
confidence: 99%